Statistical analysis angle values brachiocephalic-foream after epicondyle of the humerus fracture in children - Miśkiewicz, Piotr; Maj, Agnieszka; Świątoniowska, Natalia Alicja (Journal of Education, Health and Sport, 2017)
Statistical analysis angle values brachiocephalic-foream after epicondyle of the humerus fracture in children Summary Introduction. The brachial epithelial fractures of the humerus are typical childhood traumas. Complex anatomy and biomechanics of the elbow cause that the treatment and evaluation of the results of the epidural fractures is still being investigated. In the literature many works have been devoted to pathomechanism, types of treatment, prevention of complications. Objective. The aim was to determine the most frequently occurring deviations from the normal state after a fracture and factors affecting the distal consequences of fracture of the superficial humeral humerus. Material and methods. 282 patients with transverse epicardial displacement of the humerus were included. During the study the total number of children hospitalized due to the injury of the elbow was 488. Results. 73.3% of patients had a deviation of the shoulder and forearm angle after fracture. Valvular deformity was reported in 13.9%. 180º (cubitus rectus) arm-and-mouth angle occurred in 17.8%. The reduction of angina in the range of valvular heart disease occurred in 17.8%. Increased elbow flexion occurred in 22.8% of cases. Conclusions. The brachial epithelial fractures of the humerus account for 57.9% of all injuries to the elbow joint in children. The deviation of the brachial-forearm angle occurred in 72.3% of cases. Most of them, because 22.3% of the lumbar deformities were observed. The elbow varus occurred in 13.9% of children. The low rate of observed deformation was the result of the accepted measurement method. At the recording of each deviation, the percentage of observed cases of elbow joint increased to 49.5%.